More Results on Complementary Tree Domination Number of Graphs - S. Muthammai; P. Vidhya (International Journal of Mathematics And its Applications, 2016)
A set D of a graph G = (V, E) is a dominating set if every vertex in V-D is adjacent to some vertex in D. The domination number γ(G) is the minimum cardinality of a dominating set. A dominating set D is called a complementary tree dominating set if the induced subgraph is a tree. The minimum cardinality of a complementary tree dominating set is called the complementary tree domination number of G and is denoted by γ_ctd(G). In this paper, some results on complementary tree domination established.